2020
DOI: 10.1002/smj.3180
|View full text |Cite
|
Sign up to set email alerts
|

Selling your soul to the devil? The importance of independent ownership to identity distinctiveness for oppositional categories

Abstract: Oppositional categories emerge in direct ideological opposition to incumbent mass producers. In doing so, these oppositional categories, especially craft-based ones, emphasize their size (small),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…They frame a lack of belonging as a potential dark side of entrepreneurship. This is echoed in Mathias, Huyghe, and Williams (2020), who frame distinctiveness and belonging as oppositional. Our findings suggest that, rather than being the opposite ends of a spectrum, distinctiveness and belonging are at the core of situated entrepreneurial identities in different settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They frame a lack of belonging as a potential dark side of entrepreneurship. This is echoed in Mathias, Huyghe, and Williams (2020), who frame distinctiveness and belonging as oppositional. Our findings suggest that, rather than being the opposite ends of a spectrum, distinctiveness and belonging are at the core of situated entrepreneurial identities in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…Work has shown how ventures can be used as a vehicle in which a founder affirms and defends their social identity, pointing to the relevance of social identity in venturing decisions and behaviours (Powell and Baker 2017). Social identity literature has also explored the inner conflict that entrepreneurs experience as they are torn between their need for distinctiveness and that for belonging (Gehman and Grimes 2017;Mathias, Huyghe, and Williams 2020;Shepherd and Haynie 2009;Solomon and Mathias 2020).…”
Section: Identity Identity Work and Entrepreneurshipmentioning
confidence: 99%
“…Most of them focus on describing the CB market in Europe, Brazil and the USA, addressing the status of the CB industry, historical events, strategic approaches and growth perspectives. Mathias et al (2020) found four eras in the CB industrythe growth era (2006)(2007)(2008)(2009)(2010)(2011), the sellouts era (2011)(2012)(2013)(2014), the ambiguity era (2014-2017) and the independence era (2017-). They differentiate these eras regarding identity, code centrality, insider role, reciprocal tensions, outsider roles and identity distinctiveness.…”
Section: Qualitative Cluster Analysismentioning
confidence: 99%
“…This article documents how concerns about the social approval of relevant audiences impede the formation of firm–SMO collaborations when they cross strongly oppositional field boundaries. Oppositional organizational fields, such as social movements or oppositional market categories, form “in direct ideological opposition to the existing dominant logic embodied by incumbents” (Mathias, Huyghe, and Williams, 2020: 2549) and seek to address the problematic elements or practices of incumbents (King and Soule, 2007; Hsu and Grodal, 2021). Members of oppositional fields are thus perceived as independent challengers of incumbents.…”
mentioning
confidence: 99%